Metal Phosphides Embedded with In Situ‐Formed Metal Phosphate Impurities as Buffer Materials for High‐Performance Potassium‐Ion Batteries. Issue 40 (15th September 2021) - Ji, Shunping; Song, Chunyan; Li, Junfeng; Hui, Kwan San; Deng, Wenjun; Wang, Shuo; Li, Haifeng; Dinh, Duc Anh; Fan, Xi; Wu, Shuxing; Zhang, Jintao; Chen, Fuming; et al.
Abstract: As anodes for metal‐ion batteries, metal phosphides usually suffer from severe capacity degradation because of their huge volume expansion and unstable solid electrolyte interphase (SEI), especially for potassium‐ion batteries (PIBs). To address these issues, this study proposes amorphous phosphates acting as buffer materials. Ten types of metal phosphide composites embedded with in situ‐formed amorphous phosphates are prepared by one‐step ball milling using red phosphorus (RP) and the corresponding metal oxides (MOs) as starting materials. A zinc phosphide composite is selected for further study as a PIB anode. Benefitting from the effective suppression of volume variation, a KF‐rich SEI is formed on the electrode surface in the KFSI‐based electrolyte. The zinc phosphide composite exhibits a high reversible specific capacity and outstanding long‐term cycling stability (476 mAh g −1 over 350 cycles at 0.1 A g −1 after going through a rate capability test and 177 mAh g −1 after 6000 cycles at 1.0 A g −1 ) and thus achieves the best cycling performance among all reported metal phosphide‐based anodes for PIBs. This study highlights a low‐cost and effective strategy to guide the development of metal phosphides as high‐performance anodes for PIBs. Abstract : A universal strategy for preparing metal phosphides embedded with in situ‐formed amorphous phosphates to function as buffer materials is proposed. The existence of amorphous phosphates can effectively reduce the volume expansion of metal phosphide electrodes and improve the solid electrolyte interphase and cycling stability when used as anodes for potassium‐ion batteries in the KFSI‐based electrolyte.